BARRIERS TO THE IMPLEMENTATION OF ISONIAZID PREVENTIVE THERAPY AMONG CHILDREN UNDER FIVE YEARS OLD IN CLOSE CONTACT WITH SPUTUM SMEAR-POSITIVE TB PATIENTS - Tirsa Hizkia Saverina Nugroho; Anindita Soetadji; Dea Amarilisa Adespin; Stefani Candra Firmanti (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: The implementation of isoniazid preventive therapy (IPT) among children under five years old in close contact with sputum smear-positive TB patients is still low. Only 21,7% of children implemented the IPT in Central Java in 2017. Assessment of the barriers to IPT implementation needs to be carried out in the control of child TB cases.Objective: To analyze the barriers to IPT implementation among children under five years old in close contact with sputum smear-positive TB patients.Methods: A cross-sectional study was conducted among children (age <5 years) in close contact with sputum smear-positive TB patients. Data were collected from KRMT Wongsonegoro Hospital, Dr. Adhyatma, MPH Hospital, Puskesmas Kedungmundu, and Puskesmas Bandarharjo. Structured questionnaires were used to obtain sociodemographic information and to identify associated barriers to IPT implementation. The data were analyzed using Fisher’s exact test.Results: The majority (93,3%) of the total subject (75) of this study did not implement the IPT. The results of the bivariate analysis showed that distance to health facilities (p=0.024), perceived barriers (p=0.016), and cues to action (p=0.001) had a significant association as barriers to IPT implementation. Meanwhile age (p=0.622), gender (p=2.121), education level (p=0.073), economic level (p=0.521), knowledge level (p=0.166), and perceived threats (p=0.316) had no significant association as barriers to IPT implementation.Conclusion: IPT implementation rate is low. The barriers were distance to health facilities, perceived barriers, and cues to action.